2003
DOI: 10.1111/1475-679x.00095
|View full text |Cite
|
Sign up to set email alerts
|

Are Selling, General, and Administrative Costs “Sticky”?

Abstract: A fundamental assumption in cost accounting is that the relation between costs and volume is symmetric for volume increases and decreases. In this study, we investigate whether costs are “sticky”—that is, whether costs increase more when activity rises than they decrease when activity falls by an equivalent amount. We find, for 7,629 firms over 20 years, that selling, general, and administrative (SG&A) costs increase on average 0.55% per 1% increase in sales but decrease only 0.35% per 1% decrease in sales. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

97
1,651
17
271

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,022 publications
(2,036 citation statements)
references
References 10 publications
97
1,651
17
271
Order By: Relevance
“…Verhagem et al (2011), in a study covering the years 2005 to 2009, look for evidence of financial statement management via operating decisions in Steel and Metallurgy firms listed on the BM&FBOVESPA, as well as analysing whether the corporate governance at these companies provided an incentive or not for such management practices. Adopting the econometric models proposed by Anderson, Banker, and Janakiraman (2003) and Rowchowdhury (2006), they verify that the companies examined a priori managed their financial statements via operating decisions. Moreover, they find that corporate governance provided a counterincentive to earnings management via operating decisions, in terms of SG&A.…”
Section: Theoretical Frameworkmentioning
confidence: 78%
“…Verhagem et al (2011), in a study covering the years 2005 to 2009, look for evidence of financial statement management via operating decisions in Steel and Metallurgy firms listed on the BM&FBOVESPA, as well as analysing whether the corporate governance at these companies provided an incentive or not for such management practices. Adopting the econometric models proposed by Anderson, Banker, and Janakiraman (2003) and Rowchowdhury (2006), they verify that the companies examined a priori managed their financial statements via operating decisions. Moreover, they find that corporate governance provided a counterincentive to earnings management via operating decisions, in terms of SG&A.…”
Section: Theoretical Frameworkmentioning
confidence: 78%
“…According to the methodology of the Farm Accountancy Data Network (FADN) 1 , the data source for our study, revenue is recognized at the moment of production, which provides a better link to activity than the revenue-recognition at the moment of sale, the independent variable employed in Anderson et al (2003).…”
Section: Models Specificationmentioning
confidence: 99%
“…Empirical evidence widely support cost stickiness (e.g. Noreen and Sonderstrom, 1997;and Anderson et al, 2003). Further, Balakrishnan et al (2004), Calleja et al (2006) and Balakrishnan and Gruca (2008) studied different subjects related to cost stickiness.…”
Section: Introductionmentioning
confidence: 99%
“…Beginning with Anderson et al [1,2] (ABJ), a relatively new stream of literature has investigated the phenomenon referred to as "sticky costs." ABJ originally coined this phrase and defined it as a larger increase in costs with an increase in revenue than a decrease in costs with a corresponding decrease in revenue.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the absolute change in costs for an increase in sales was larger than the absolute change in costs for a decrease in sales. This equates to a negative β 2 in equation (1). The authors opined that this may be evidence of a deliberate managerial hesitation to reduce costs in the face of a decrease in sales.…”
Section: Introductionmentioning
confidence: 99%